Research on linearization modeling technology based on large-signal scattering function - HUA Xiao-jie; LIN Mao-liu; SUN Hong-jian (Tongxin xuebao)
Based on nonlinear large-signal scattering functions theory,some notable characters of RF-amplifier when op-erated on nonlinear regime were described. In case of weakly nonlinear device,a novel method to combine phase nor-malization and linearization of scattering functions was presented,which looks similar to classical scattering parameters for modeling nonlinear device under test （DUT）. Moreover,the reasons were analyzed for the distortion of response and relate it with the emergence of conjugate term. Finally,it prove that the response to the conjugate term of the small input excitation is not negligible and conclude with the efficiency of the model.